From plant survival to thriving: exploring the miracle of brassinosteroids for boosting abiotic stress resilience in horticultural crops - Zhang, Zhilu; Chen, Zhongyu; Song, Haina; Cheng, Shiping (Frontiers in Plant Science, 2023)
Abiotic stresses pose significant threat to horticultural crop production worldwide.These stresses adversely affect plant growth, development, and ultimately declined crop growth, yield and quality. In recent years, plant scientists have been actively investigating innovative strategies to enhance abiotic stress resilience in crops, and one promising avenue of research focuses on the use of brassinosteroids (BRs). BRs are a class of plant hormones that play crucial roles in various physiological processes, including cell elongation, differentiation, and stress responses. They have emerged as potent regulators of plant growth and development, and their role in improving abiotic stress tolerance is gaining considerable attention. BRs have been shown to mitigate the negative effects of abiotic stresses by modulating key physiological and biochemical processes, including stomatal regulation, antioxidant defense, osmotic adjustment, and nutrient uptake. Abiotic stresses disrupt numerous physiological functions and lead to undesirable phenotypic traits in plants. The use of BRs as a tool to improve crop resilience offers significant promise for sustainable agriculture in the face of increasing abiotic stresses caused by climate change. By unraveling the phenomenon of BRs, this review emphasizes the potential of BRs as an innovative approach for boosting abiotic stress tolerance and improving the overall productivity and quality of horticultural crops. Further research and field trials are necessary to fully harness the benefits of BRs and translate these findings into practical applications for crop production systems.